KERENTANAN AIRTANAH UNTUK PENYIMPANAN LIMBAH RADIOAKTIF DEKAT PERMUKAAN DI DESA MUNCUL KECAMATAN SETU KOTA TANGERANG SELATAN - , ENVIRA NUR UTAMI, Prof. Dr. Suratman Worosuprojo, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Low level radioactive waste is an output of human activity. Radioactive waste has a different characteristic than other kinds of waste, then it needs a special treatment like a research about groundwater vulnerability. Groundwater is a basic need for human, therefore it needs a proper place to store. Groundwater vulnerability divided into static and dynamic level. Static Groundwater vulnerability only consider with DRASTIC parameter such as depth of water table, recharge, aquifer media, soil media, topography, impact of vadose zone, and conductivity. While dynamic groundwater vulnerability also consider about land use. Based on static groundwater vulnerability, most of (75%) of the area (groundwater) in Desa Muncul counted as medium level of groundwater vulnerability. While based on dynamic groundwater vulnerability, most of (50%) of the area (groundwater) in Desa Muncul counted as not vulnerable. Key word : DRASTIC, groundwater vulnerability, waste, pollution